El Tunal Experimental: 40 Years Later an Experimental Housing Project in Bogotá, Colombia, 1972 - Bermudez, Ramón; Bermudez, José Roberto; Sanjinés, Daniela (Docomomo Journal, 2014)
At the beginning of the 70s in Bogotá, Colombia, an experimental housing project tried to respond, with adaptable and intelligent solutions, to the challenges of an increasingly urbanized country. It utilized a Low-Rise, High-Density (LRHD) urban system that enhanced the flexibility and the incremental process of housing units cells. This paper aims first, to explain the historical background and the objectives of an experimental project in a Latin American context; then to expose its innovative architectural proposals and finally, to evaluate its evolution in its 5th decade of existence.